Síntese de aluminas macro-mesoporosas pelo método sol-gel acompanhado de separação de fases - Rodrigues, Jorge do Carmo [UNESP] (2015)
The production of alumina with volume and size distribution of pores controlled by phase separation induced by the addition of the polymer polyethylene oxide (PEO) during synthesis is an emerging issue in the area of functional ceramics. The aluminas were produced by the sol-gel process followed by phase separation, and the PEO as inducing agent phase separation and propylene oxide to gelation. Conditions for kinetic and thermodynamic control over these events were kept by controlling the stirring time and temperature in the reaction medium. Synthesis routes have been optimized by adjusting the preparation parameters varying the concentration of pores directing agent (PEO) during sol-gel process. This transformation was accompanied by in-situ SAXS and the results reveal the growth typical of fractal objects starting from a diluted solution, whose dimensionality in the Porod region was 1,7, characteristic of aggregation controlled by diffusion and the distances between the growing particles is around 2,95 nm. Gamma alumina (-Al2O3) with diversified porous texture and macro-mesopores was obtained with thermal treatment up to 700 ° C, being supported by several techniques. The macro-mesoporosity can be adjusted by PEO driver pores agent in a molar ratio from 0,01 to 0,07. Molar ratios of PEO above 0,07 produces only mesopores, decreasing the cumulative volume of this pores when the molar ratio increases from 0,08 to 0,1. These mesoporous aluminas had higher specific surface area (BET Area  305 m² / g) and better ratio OH/O-Al compared to the macro-mesoporous.